REPRESENTAMEN IN HYPERREAL FRAMINGS OF BORGES - Magan, Rhodora G (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 18 No. 1, 2015, 2015)
The culture that has emerged since the 20th century is that of a multi-layered agenda where a fixed point is nowhere to be found. Constant innovation in every aspect of life breeds consistent replication of either tangible or tangible representamen that have virtually built hyperreality. It is a condition when one can longer determine the exact idea. In the context of multiple reproduction, ideas undergo countless alterations toward the goal of perfection. Thus uncertainty is the natural byproduct of several attempts to arrive at the desired end. This study investigates the representamen in hyperreal situations in Borges’ narratives, as these are direct referents of unstable ontology.